Catalytic Role of Refractory Interstellar Grain Analogs on H2 Formation - Suhasaria, Tushar; Mennella, Vito (Frontiers in Astronomy and Space Sciences, 2021)
Refractory dust grains have an important role to play in the chemistry of star and planet-forming regions. Their surfaces interact with interstellar gas and act as a catalyst for the formation of simple and complex molecules in space. Several mechanisms have been invoked to explain how molecular hydrogen is formed in reactions on dust grain surfaces in different regions of space. In this article, we give an overview of our understanding of the laboratory experiments, conducted over the last 20 years, that deal with H$_2$ formation on interstellar grain analogs in space simulated conditions.